Leadership sensegiving and leadership promotion of sensemaking: an analysis of the moderated mediation on team conflicts and implications on team effectiveness - Haddad, Lia Monnerat (2019)
In the current world, where most of the work inside organizations is completed through teamwork, team effectiveness becomes an important indicator of organizational performance, in which leadership behavior has a strong influence. The present study aims to analyse the combined effect of leadership sensegiving and the promotion of team sensemaking on the relationship between intragroup conflicts (relational and task) and team effectiveness. In the existing literature there are several studies on the types of conflicts and their positive and negative impacts on team effectiveness, as well as leadership sensegiving and the promotion of sensemaking. However, there are not yet many studies analyzing these specific leadership behaviors in conflict situations as predictors of team effectiveness. A moderated mediation model is proposed to analyze the combined effects of leadership sensegiving and the promotion of team sensemaking on intragroup conflicts (relationship and task) as predictors of team effectiveness. When conducting the study in 55 teams, however, the results found did not support the proposed model. Nevertheless, the results did show a significant effect of the leadership promotion of sensemaking as a simple moderator in the relationship between leader sensegiving and relationship conflicts. More specifically, when there is a high level of leadership promotion of sensemaking and low level of leadership sensegiving, relationship conflict is negatively affected, decreasing its occurrence.